Antecedents Of Organizational Commitment: A Study Among The Hotels In Malaysia - Asokan, Kartiban (2014)
This research is conducted to study on the antecedents of organizational commitment. This study was conducted among the hotel employees in Malaysia. This study was carried out as a cross sectional study for about five months. A total of 430 questionnaires were distributed to the hotel employees across the Malaysia via face to face data collection and also via email response. In order to test the relationship between variables, the data collected from the respondents were analysed using numerous statistical techniques such as descriptive statistics analysis, factor analysis, reliability analysis and multiple linear regression by analysing using the Statistical Package for Social Science 22 (IBM SPSS Statistics 22).